?EFFECT OF CCC SEED TREATMENT ONTHE GROWTH OF RICE ANDWHEAT (Biological Sciences - PJSIR, 1999)
Effects ofCCC seed treatment on the growth of rice and wheat seedlings were assessed in controlled conditions. Seeds were soaked for 24.h in 0, 10, 25, 50, 100 and 200 ppm CCC solutions. The growth of rice seedling, particularly the number of axes was enhanced significantly by CCC, maximum enhancements being caused by higher concentrations of I00 and 200 . ppm. The number of laterals and total root length of rice seedlings was also increased considerably. In contrast. shoot as well as root growth of wheat was suppressed by the CCC treatment. With an increase inCCC concentration. acorresponding and highly significant retardation in shoot height and shoot and root dry weight of wheat seedlings was observed.